PENDEKATAN PEMBELAJARAN BERBASIS PERMAINAN SEBAGAI UPAYA MENINGKATKAN KECERDASAN MATEMATIKA SISWA - Mariatul Kiftiah; Nilamsari Kusumastuti; Bayu Prihandono; Yundari Yundari; Helmi Helmi; Evi Noviani; Fransiskus Fran; Yudhi Yudhi; Meliana Pasaribu; Nur’ainul Miftahul Huda (Jurnal Abdimas Bina Bangsa, 2024)
The perception of mathematics as a compulsory subject in school is often negative. To address this challenge, a service-learning initiative was implemented at SMAN 1 Sambas, employing a game-based pedagogy. Mathematics seminars and exhibitions were organized by Mathematics Study Program to enhance students' engagement and comprehension of mathematical concepts. The effectiveness of this approach was evaluated through a questionnaire, which revealed a high level of approval among students regarding the relevance, motivation, understanding of mathematical principles, problem-solving abilities, and playing skills in mathematics learning. This approach is expected to change students’ perception of mathematics and improve their learning outcomes